2018
DOI: 10.20944/preprints201801.0219.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Shot-Peening and Stress Ratio on the Fatigue Crack Propagation of AL 7475-T7351 Specimens

Abstract: Shot peening is an attractive technique for fatigue enhanced performance of metallic components, because it promotes crack initiation retardation and later crack growth. Engineering design based on fatigue crack propagation predictions applying the principles of fracture mechanics is commonly used in aluminum structures for aerospace engineering. The main purpose of present work was to analyze the effect of shot peening on the fatigue crack propagation of the 7475 aluminum alloy, under both constant amplitude … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Subsequently, Zhang and Ma evaluated the effect of carbon nanofiber (CNF) content on fracture toughness of phenolic syntactic foams, The fracture toughness increased with the increase in CNFs content and the decreasing trend occurred beyond 1.5 vol % of CNFs addition ascribed to the agglomeration and clustering of CNFs. Ferreira et al . filled epoxy syntactic foams with short fiber to discuss the addition of short fiber on the mechanical behavior of composites.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Zhang and Ma evaluated the effect of carbon nanofiber (CNF) content on fracture toughness of phenolic syntactic foams, The fracture toughness increased with the increase in CNFs content and the decreasing trend occurred beyond 1.5 vol % of CNFs addition ascribed to the agglomeration and clustering of CNFs. Ferreira et al . filled epoxy syntactic foams with short fiber to discuss the addition of short fiber on the mechanical behavior of composites.…”
Section: Introductionmentioning
confidence: 99%
“…In this figure, glass fibers with an average length of 106 μm and microspheres with an average diameter of 60 μm randomly distribute in the matrix, and a few fibers are exposed. Many literatures cover such composites . Although the model of fibers and microsphere uniform distribution is simple, it is not consistent with the actual situation.…”
Section: Methodsmentioning
confidence: 99%
“…They showed that the tensile strength and flexural strength of the composites were enhanced with increasing fiber volume fraction. Ferreira et al . prepared composites with hollow glass microspheres and random fiber filling in epoxy resin, in which the volume fraction of the fibers could reach as high as 1.2%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, three methods are used to design supermirrors, which are called the Mezei method [8,9], Kozhevnikov method [10,11], and block method [12][13][14]. The supermirrors used in NuSTAR [15] and ATHENA [16,17] were designed by the Mezei method. And the supermirror used in ASTRO-H [14] was designed by block method.…”
Section: Introductionmentioning
confidence: 99%